2007
DOI: 10.1111/j.1748-1716.2007.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of slow delayed rectifier K+‐current in QT prolongation in the alloxan‐induced diabetic rabbit heart

Abstract: It is concluded that type 1 diabetes mellitus, although only moderately, lengthens ventricular repolarization. Diabetes attenuates the repolarization reserve by decreasing the density of I(Ks) current, and thereby may enhance the risk of sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
(54 reference statements)
1
34
2
Order By: Relevance
“…This work is performed in an animal model (rat) which has only part of the cardiac K + repolarizing currents present in human heart (I to and IK 1 ). Different works carried out in different animal models showed that IK 1 is not affected by diabetes, IK s is slightly reduced, IK r is slightly or no reduced, and I to is reduced by half, being this last the main responsible for the action potential alterations found in diabetic hearts [2,14,40,41]. However, based on the results obtained with I to , we can expect that the intracellular regulation of the other channels would be impaired in diabetic hearts as well.…”
Section: Discussioncontrasting
confidence: 40%
“…This work is performed in an animal model (rat) which has only part of the cardiac K + repolarizing currents present in human heart (I to and IK 1 ). Different works carried out in different animal models showed that IK 1 is not affected by diabetes, IK s is slightly reduced, IK r is slightly or no reduced, and I to is reduced by half, being this last the main responsible for the action potential alterations found in diabetic hearts [2,14,40,41]. However, based on the results obtained with I to , we can expect that the intracellular regulation of the other channels would be impaired in diabetic hearts as well.…”
Section: Discussioncontrasting
confidence: 40%
“…In contrast, the CV at [K + ] o =4 mM was significantly slower (by ≈13%) in diabetic hearts, compared to controls (CV = 0.53±0.02 m/s in control vs. 0.46±0.02 m/s in diabetes, p<0.05). Some earlier studies suggested that I Kr was reduced in diabetic hearts [13,14], whereas others observed no change [12,15]. Since the conductance of I Kr is proportional to the square root of [K + ] o [34], we hypothesized that stressing the heart with changes in [K + ] o would exacerbate any differences in APD between control and diabetic hearts.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, Lengyel et al [12] showed a small increase in QTc, and a reduced density of I Ks in the diabetic rabbit hearts, but observed no alterations in the density/properties of I Kr . In the canine model of diabetes, only little to moderate QTc and APD prolongation were shown, with decreases in I to and I Ks , but no change in I Kr was observed [15].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Diabetes is a significant independent risk factor for heart failure and there are a substantial number of patients with both diabetes and heart failure [4]. The most well documented electrophysiological dysfunction of type I diabetes is a prolongation of the QT interval in the electrocardiogram [2], which is a direct effect of the prolongation of the ventricle action potential [5]. One of the less thoroughly studied effects of type I diabetes is related to the conduction of electrical activation through the heart.…”
Section: Introductionmentioning
confidence: 99%